Diffusion Tractography of the Cervical Spinal Cord by Using Parallel Imaging - Tsuchiya, Kazuhiro (AJNR Am J Neuroradiol, 2005)
Summary: We applied a single-shot echo-planar axial diffusion tensor sequence with parallel imaging for tractography of the cervical cord. Placing a large region of interest on a reconstructed sagittal image, the cervical cord was depicted as a tract bundle showing color-encoded cephalocaudally. By setting one region of interest in the cerebral peduncle and another in the entire cord on source images, tracts on each side were visualized. This method is promising for tractography of the cervical cord.